2020
DOI: 10.13106/jafeb.2020.vol7.no10.1081
|View full text |Cite
|
Sign up to set email alerts
|

Financial Capability and Differences in Age and Ethnicity

Abstract: The objective of this study is to disclose the effect of socio-demographic characteristics such as, age and ethnicity which is comprised of Malay, Chinese, Indian and Others on four financial capability domains namely planning ahead, managing money, choosing products and staying informed. A closed ended self-administered questionnaire was disseminated to a total of 2000 respondents among four types of groups which consist of FELDA or rural area residents, private sector employees, government sector employees a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 11 publications
(14 reference statements)
0
16
0
1
Order By: Relevance
“…Prior this, in early 2020, the Bank of Finland was given the key responsibility of coordinating a national strategy for improving financial literacy of Finns, including a plan for activities in financial education as longer-term national objectives (Bank of Finland, 2020). This need is more prevalent as ever as young people lack the financial capability that older people have (Xiao et al, 2015), and which can alleviate COVID-19 generated financial anxiety (Mokhtar et al, 2020) and financial fragility (Lusardi et al, 2020). Both momentary and long-term actions are needed for youth security and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Prior this, in early 2020, the Bank of Finland was given the key responsibility of coordinating a national strategy for improving financial literacy of Finns, including a plan for activities in financial education as longer-term national objectives (Bank of Finland, 2020). This need is more prevalent as ever as young people lack the financial capability that older people have (Xiao et al, 2015), and which can alleviate COVID-19 generated financial anxiety (Mokhtar et al, 2020) and financial fragility (Lusardi et al, 2020). Both momentary and long-term actions are needed for youth security and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…The study reported that the Chinese possessed better financial behavior than Malay and India. In contrast, Mokhtar et al (2020) also stated that there was no difference in financial capabilities and financial planning among the ethnic group. Malaysia is a multi-ethnic country which consisted of three major groups, Malay, Chinese and India.…”
Section: Literature Reviewmentioning
confidence: 97%
“…This study also reports that business and accountancy students have higher achievements in financial literacy. Ethnicity is often not addressed in America; however, it has been shown that different races have different spending behaviors and attitudes toward financial literacy in Malaysia (Mokhtar et al , 2020). The study reported that the Chinese possessed better financial behavior than Malay and India.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hal tersebut juga didukung oleh ekonomi keuangan kelas menengah ke atas. Masyarakat yang berpenghasilan cukup besar mungkin tidak dapat mengelola pengeluaran keuangannya dengan baik, hal ini terjadi karena perilaku ekonomi yang tidak bertanggung jawab dan adanya praktik belanja yang impulsi (Haerani et al, 2019;Bulutoding et al, 2020;Mokhtar et al, 2020;Sudarsono et al, 2020).…”
Section: Pendahuluanunclassified